Intravital microscopy: Imaging host-parasite interactions in the brain - Niz, Mariana De; Nacer, Adéla; Frischknecht, Friedrich (Cellular microbiology, 2019)
Intravital fluorescence microscopy (IVM) is a powerful technique for imaging multiple organs, including the brain of living mice and rats. It enables the direct visualisation of cells in situ providing a real-life view of biological processes that in vitro systems cannot. In addition, to the technological advances in microscopy over the last decade, there have been supporting innovations in data storage and analytical packages that enable the visualisation and analysis of large data sets. Here, we review the advantages and limitations of techniques predominantly used for brain IVM, including thinned skull windows, open skull cortical windows, and a miniaturised optical system based on microendoscopic probes that can be inserted into deep tissues. Further, we explore the relevance of these techniques for the field of parasitology. Several protozoan infections are associated with neurological symptoms including Plasmodium spp., Toxoplasma spp., and Trypanosoma spp. IVM has led to crucial findings on these parasite species, which are discussed in detail in this review.
Gesehen am 15.05.2019